2002
DOI: 10.1210/en.2002-220182
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Modulates Nuclear Factor-κB Activation in Hippocampus of Diabetic Rats

Abstract: Oxidative stress induced by chronic hyperglycemia contributes to cerebrovascular complications in diabetes. Reactive oxygen species activate the transcription factor nuclear factor-kappaB (NF-kappaB), which in turn activates a variety of target genes linked to the development of diabetic complications. Dehydroepiandrosterone, an adrenal steroid, which possesses a multitargeted antioxidant effects, is also synthesized de novo by the brain. Normoglycemic and streptozotocin-diabetic rats were either treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 52 publications
3
47
0
1
Order By: Relevance
“…Moreover, antioxidants prevent the decrease of MCK transcription in skeletal muscle cells (15). It has been shown that dehydroepiandrosterone (DHEA), a multifunctional steroid secreted by the adrenal gland and brain (16), possesses a multitargeted antioxidant effect (17,18) and prevents tissue damage induced by acute and chronic hyperglycemia (19).…”
mentioning
confidence: 99%
“…Moreover, antioxidants prevent the decrease of MCK transcription in skeletal muscle cells (15). It has been shown that dehydroepiandrosterone (DHEA), a multifunctional steroid secreted by the adrenal gland and brain (16), possesses a multitargeted antioxidant effect (17,18) and prevents tissue damage induced by acute and chronic hyperglycemia (19).…”
mentioning
confidence: 99%
“…PRT is known to exert an anti-NF-B effect by inactivating inhibitory kB (IkB) kinase (Kwok et al 2001). DHEA, in contrast, may inhibit NF-B through its antioxidant effect by altering the intracellular redox state (Gao et al 2005, Kabe et al 2005, through inhibition of I B ubiquitination is shown in diabetic rats (Aragno et al 2002), or through activation of PPAR (Kochan & Karbowska 2004). Thus, we assume that the combined effects of the two drugs are caused, at least partly, by their inhibitory effects on NF-B function, although the effects on other signaling pathway(s) are not ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…95% ethanol mixed with 8 vol. mineral oil) (Aragno et al 2002) were administered subcutaneously for 21 days from 1 week after AtT20 cell injection. At the end of the experiment, mice were killed, and tumor weights were measured after their careful resection and the tumors and livers were used for quantitative RT-PCR assay.…”
Section: Xenograft Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, DHEA was found to potently inhibit NF-B activation by affecting NF-B itself and IB, at least partly through its effect on redox balance (23)(24)(25).…”
mentioning
confidence: 99%